Housework in Peru: Working Transitions, Education and Economic Cycle - Garavito, Cecilia (2016)
The aim of this work is to analyze the transitions from paid housework toward other occupations, unemployment and inactivity, and the determinants of these transitions. We use the panel data from the ENAHO for the periods 1998-2002, 2002-2006, and 2007-2011. After a detailed descriptive analysis of partial and complete panels, we find that around one third of the paid house-workers stay in this occupation while a similar percentage moves to independent work or low productivity salaried work. After estimating the transitions from paid housework to other occupations, and to inactivity, we find that a higher level of education is always related to a transition toward another occupation, although in the case of paid house-workers it is usually toward independent labor. Finally, transitions from paid housework to other occupations or inactivity depend on the economic cycle, although the marginal effects are lower for them than for women in general.